Use of Communication Pattern in State Agricultural University Students about Jobs - Singh, Shesh Narain; Doharey, R. K.; Sonkar, S. P.; Verma, G.S.; Gautam, M.P.; Gautam, Shrestha (Indian Journal of Extension Education, 2018)
This study was conducted in 4 main agricultural universities in Uttar Pradesh by interviewing 300 respondents who were selected through proportionate random sampling technique on the criteria of having four year degree programme of B.Sc.(Ag.), two year degree programme M.Sc.(Ag.) and three year programme Ph.D.(Ag.). The study depicted that the most use of communication media of respondents with mobile phone. An over whelming majority of the respondents were found using cellular phone as their main source of communication. The maximum number of respondents (62%) was observed in medium (3 to 7 hours) category of communication technology use in day, 35 per cent satisfied, familiarity with communication technologies was television and most usefulness of communication technologies in career preferences was mobile phone. The majority Purpose in use of communication Technology was computer information retrieval or data updating.
Keywords: Communication pattern; state agricultural universities